2016
DOI: 10.1371/journal.ppat.1005727
|View full text |Cite
|
Sign up to set email alerts
|

Adapting SHIVs In Vivo Selects for Envelope-Mediated Interferon-α Resistance

Abstract: Lentiviruses are able to establish persistent infection in their respective hosts despite a potent type-I interferon (IFN-I) response following transmission. A number of IFN-I-induced host factors that are able to inhibit lentiviral replication in vitro have been identified, and these studies suggest a role for IFN-induced factors as barriers to cross-species transmission. However, the ability of these factors to inhibit viral replication in vivo has not been well characterized, nor have the viral determinants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 43 publications
2
17
0
Order By: Relevance
“…Recently, we examined the sensitivity of a panel of adapted and unadapted SHIVs to IFNα in macaque lymphocytes and found that the unadapted SHIVs were potently inhibited by IFNα despite encoding the SIV antagonists of known restriction factors [25]. In contrast, SHIVs encoding adapted HIV-1 variants were largely resistant to IFNα.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we examined the sensitivity of a panel of adapted and unadapted SHIVs to IFNα in macaque lymphocytes and found that the unadapted SHIVs were potently inhibited by IFNα despite encoding the SIV antagonists of known restriction factors [25]. In contrast, SHIVs encoding adapted HIV-1 variants were largely resistant to IFNα.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Transmitted/Founder (T/F) viruses have been shown to be IFN-resistant (Fenton-May et al, 2013;Iyer et al, 2017). Furthermore, adapting SHIVs to rhesus macaques (RMs) selects for Env-mediated IFNα-resistance (Boyd et al, 2016). Additionally, inhibition of the IFN-response by administration of a IFNα receptor antagonist has been shown to result in high viral loads during acute infection and faster progression to AIDS in a pathogenic SIV-RM model (Sandler et al, 2014).…”
Section: Possible Role Of Interferon Response In Control Of Macaque-tmentioning
confidence: 99%
“…Viral envelope has also demonstrated the capacity of overcoming host restrictions beyond virus entry. For example, passage of SIV/HIV chimeric virus (SHIV) in macaques in the presence of interferon-α led to the selection of interferon-α-resistant SHIV [98]. This resistance phenotype was mapped to viral Env protein that had a higher level of expression from the resistant virus.…”
Section: Env Protein Fights Back: Evasion Of Host Restriction On Vmentioning
confidence: 99%